Tourism and Economic Growth in Malaysia - Hashim, Asmawi; Rambeli@Ramli, Norimah; Jalil, Norasibah Abd.; Hashim, Emilda (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to build a model of long-term relationship estimation between the number of tourist arrivals, foreign exchange rates, total trade in goods and services and total tourism receipts on economic growth in Malaysia. In order to achieve the objective of this study, the annual time series data is utilized. For the estimating model, this study uses the Ordinary Least Square (OLS). The findings suggest that there is a significant and positive relationship between total tourist arrivals and total trade in goods and services with economic growth. However, there is a significant and negative relationship between foreign exchange rates and total tourism receipts with economic growth. Generally, the results of this study show that there is a long-term relationship between all independent variables and economic growth in Malaysia. Based on the findings, the significant suggestion especially on Ministry of Tourism and Culture Malaysia in improving the country's economic performance through the tourism sector.